EFICACIA JURÍDICA DEL SIMPLE RETRASO EN EL CUMPLIMIENTO DE OBLIGACIONES EN EL ORDENAMIENTO ESPAÑOL - Domínguez Luelmo, Andrés (2022)
This paper briefly has analyzed the simple delay in performance of obligations, that is to say, the non–observance of the time for the performance without the debtor being in arrears. In particular, the authors defend not only the quality of non–performance of the simple delay, but also its legal effectiveness, in contrast to the various voices of Spanish doctrine that suggest its legal irrelevance when it is not invigorated by mora debitoris.